Tanggap Pertumbuhan Vegetatif dan Generatif Bawang Merah Terhadap Konsentrasi Dan Lama Perendaman GA 3 Di Dataran Rendah - Andrio Sorensen; Mariati Mariati; Luthfi A. M Siregar (Universitas Sumatera Utara, 2015)
The aim of the research was to identify the suitable concentration and soaking duration time of GAto induce flowering and seed formation of Medan variete shallots. Research was conducted atSelamat Ketaren #100 Medan which about 25 meters above sea level, begun December 2013 untilMarch 2014. The experiment was carried out by using non factorial randomized block design,replicated three times. The treatments were G0 (Control); G1 (20 ppm soaked 30 minutes GA); G2(20 ppm soaked 60 minutes GA3); G3 (20 ppm soaked 90 minutes GA); G4 (40 ppm soaked 30minutes GA3); G5 (40 ppm soaked 60 minutes GA33); G6 (40 ppm soaked 90 minutes GA); G7 (60ppm soaked 30 minutes GA3); G8 (60 ppm soaked 60 minutes GA) and G9 (60 ppm soaked 90minutes GA33). Parameters observed were shoot lenght, leaf number, tiller number, fresh weight ofbulb per sample and plot, and dry weight of bulb per sample and plot. The result showed that allparameters observed were not significantly affected by the treatments. Keywords : Shallot, GA3, Soaking Duration Time. 333